Judaism and Jesus - Garber, Zev (Cambridge Scholars Publishing, 2020)
"Teaching Jewish studies" / Zev Garber -- "Jesus in the trenches / Zev Garber -- "One in Christ" / Zev Garber -- "Jewish Jesus: partisan's imagination" / Zev Garber -- "Jesus, the Pharisees and the sages" / Kenneth Hanson -- "The shema, the historical Jesus and messianic Judaism" / Kenneth Hanson -- "Threading the needle: the Ḥasidim and the Nazarene" / Kenneth Hanson -- "Perpetual dilemma" / Zev Garber -- "Sitting at a common table" / Kenneth Hanson.